Особливості імплементації положень Кіотської конвенції у вітчизняну практику здійснення митної справи - Руда, Т. В.; Ruda, Tatiana (КНТУ, 2014)
У статті проаналізовано основні положення Кіотської конвенції з позиції їх імплементації в українське митне законодавство. Проаналізовано митну термінологію, наведену у Загальному додатку Кіотської конвенції та наведено задекларовані у ній основні напрями спрощення митних процедур. Окрім того, в статті окреслено основні проблемні моменти на шляху узгодження українського та міжнародного митного законодавства та визначено практичні напрацювання у даній сфері. The aim of the paper is to analyze the main provisions of the Kyoto Convention and outline problematic issues of Ukrainian integration into the regulatory framework in the field of customs. This paper examines the main provisions of the Kyoto Convention on the position of their implementation to Ukrainian customs legislation. Customs analyzed the terminology given in the General Annex of the Kyoto Convention and declared it defined the main directions of the simplification of customs procedures. In addition , the article outlines the main bottlenecks in the way of harmonization of Ukrainian and international customs laws and identifies best practices in this area. According to the study , it is reasonable to conclude that the provisions of the Kyoto Convention aimed at improving communication links between customs authorities and economic operators that aims to simplify, unify and reduce the costs of customs procedures. Implementation of its provisions in domestic practice will help bring Ukraine closer to the European standards of management and enhance the development of international cooperation.
Features implementing the provisions of the Kyoto Convention in domestic practice in customs matters
Keywords: кіотська конвенція; гармонізація; спрощення митних процедур; митні формальності; митне оформлення; митний контроль; статус уповноваженого економічного оператора; kyoto convention; harmonization; simplification of customs procedures; customs clearance; customs control; the status of authorized economic operator